Jogos de inversão, jogos de poder: uma etnografia online sobre práticas de feminização masculina em contexto sado-fetichista - Silva, Marcelle Jacinto da (2015)
This thesis aims to grasp the symbolic universe of erotic power games listed under the feminization of male name, a set of rituals that are part of the BDSM universe, or erotic sadomasochism, or even sado-fetishism. The purpose of this research is through ethnographic research of these practices through narratives accessed from personal blogs posts and interviews, understand the gender crossings that are triggered, negotiations and feminization of masculinity rituals that make up this universe. I use as material background from websites, blogs and Facebook profiles on the sado-fetishism theme and practices related to feminization: male submission, FemDom, among others, in order to contextualize the object of analysis, the performances of genre that happen in and out of these practices and experiences of feminization, "forced". It is therefore ethnographic description of erotic power games under the term male submission on the Internet, which are constituent elements of rituals male feminization, analyzed in this dissertation. There is a vast amount of material on male submission on the network, but little material on national practices of male feminization and forced feminization. Practices involving submission, among them the very feminization present ritualistic settings; the way practices are treated as "training", "ritual", "label", "training", "preparation", "discipline", "domestication". I chose to consider the material produced in Brazil as a way to explain the impossibility of embracing the entire phenomenon registered on the Internet.